PENERAPAN METODE MUSLE DALAM MEMPREDIKSI HASIL SEDIMEN DI SUB DAS GARANG HULU PROVINSI JAWA TENGAH (Geo-Image, 2013)
Changes in ecosystems with cultivation in Sub DAS Garang Hulu led to problems of erosion in the uplands and sedimentation in downstream areas, so it needs to be done through the calculation of the prediction results of the sediment. The purpose of this study is to calculate the sediment in Garang Hulu using MUSLE (Modified Universal Soil Loss Equation). The results showed the results of sediment (sediment yield) is out of Garang Hulu varies. The largest sediment occurred on February 6, 2010 at 23.1313 tons / events and the smallest occurred on February 15, 2010 amounted to 1.4025 tons / occurrence of rain events on 19 January to 4 March 2010. Prediction the result of analysis using the method MUSLE with constanta a = 11.6 and b = 0.56 shows that results are significantly different from an analysis using field measurements. Having made application for a method with constants a = 309.350 b = 0.332 and the results obtained sediment was not significantly different from field measurements at 95% significance level. While the application of the method remains significantly different from the results of field measurements of sediment due to the high surface flow